Psychometric Evaluation of Cancer Patients - S B Bansal; Sanjay Dixit; Geeta Shivram (Medsci Publications, 2012)
Background: Mental health is the balanced development of the individual's personality and the emotional attitude which will enable him or her to live harmoniously with his or her Fellow citizens. Mental health is not exclusively a matter of relation between persons It is also a matter of relation of individuals towards the community in which they live, towards the society of which the community is a part, and towards the social institutions which for a large part guide their life, determine their way of living, working, leisure, and the way they spends and earns the money, the way they sees happiness, stability and security. Objective: To asses and quantify the prevalence of psychological morbidity in cancer patients of government cancer hospital MGM Medical College Indore, M.P. Material and Methods: 100 cancer patients were chosen randomly all of them were interviewed through a questionnaire survey in ward and OPD of cancer hospital in November and December 2009. Data on demographics, and duration of diagnosis were collected. Results: Gender wise prevalence of psychological morbidity Grade II &III were 94% in males and 86% in females. Chi square test was not significant. According to age the Grade II & III psychological morbidity were 41(46%) in 15-45 years age group and 49 (54%) in 46-75 years age group which is significantly higher than previous age group .Chi square test (x2 = 7.54) p value < 0.05 Grade II & III psychological morbidity were 52% in 0-6 months duration while it was 38% in more than 6 months duration Chi square test (x2= 8.04), P value < 0.05 statistically significant. Conclusion: the prevalence of psychological morbidity was slightly higher in males and older age group, and also high psychological morbidity was seen in recently diagnosed cancer patients. A good counseling, stress relaxation and life style modification program is required to make such patients live their life in a positive and better way.